Comparative study of natural fiber-Reinforced composites for sustainable thermal insulation in construction - Sheymaa Alazzawi; Walaa A. Mahmood; Suha K. Shihab (International Journal of Thermofluids)
Natural fiber-reinforced composites are increasingly recognized as sustainable alternatives in construction materials due to their environmentally friendly properties and ability to increase thermal insulation. This study conducts an in-depth comparative study between palm fiber (DPF) composites and other natural fiber-reinforced composites, including hemp and jute, with a focus on their application as insulation that provides insight into their thermal properties, performance, and mechanical properties to inform sustainable construction practices. The research methodology involves constructing and producing composite samples using date palm, hemp, and jute fibers, each combined into a common base material. Composites are mold-made, ensuring consistent and reproducible samples for testing. Through a systematic investigation, we explore these composites' thermal, and mechanical properties. Testing covers a specific range of fiber loadings, from 10 wt % – 30 wt %. Specific characterization techniques, including compression test, bending test, impact, FT-IR, and DSC, were used to evaluate the behavior of the composites under various conditions. Our results show that the thermal conductivity of the composites ranges from 0.0514 – 0.084 W/m. K for different fiber loading is affected by the fiber content.Furthermore, at maximum fiber concentration (30 by weight), the highest heat capacity of the hemp composite was 1674 J/Kg.K. The 30 wt % of jute and date palm composites achieved a maximum compressive strength of (70 MPa) and (64 MPa) respectively.In summary, this comprehensive study demonstrates the potential of natural fiber-reinforced composites as sustainable and fully bio-based alternatives for construction-related applications. Superior thermal properties and improved mechanical strength highlight their viability in thermal insulation applications.